Comparison of gene expression profiles between human erythroid cells derived from fetal liver and adult peripheral blood - Tangprasittipap, Amornrat; Kaewprommal, Pavita; Sripichai, Orapan; Sathirapongsasuti, Nuankanya; Satirapod, Chonthicha; Shaw, Philip J.; Piriyapongsa, Jittima; Hongeng, Suradej (PeerJ (San Francisco, CA), 2018)
A key event in human development is the establishment of erythropoietic progenitors in the bone marrow, which is accompanied by a fetal-to-adult switch in hemoglobin expression. Understanding of this event could lead to medical application, notably treatment of sickle cell disease and -thalassemia. The changes in gene expression of erythropoietic progenitor cells as they migrate from the fetal liver and colonize the bone marrow are still rather poorly understood, as primary fetal liver (FL) tissues are difficult to obtain. We obtained human FL tissue and adult peripheral blood (AB) samples from Thai subjects. Primary CD34 cells were cultured in a fetal bovine serum-based culture medium. After 8 days of culture, erythroid cell populations were isolated by flow cytometry. Gene expression in the FL- and AB-derived cells was studied by Affymetrix microarray and reverse-transcription quantitative PCR. The microarray data were combined with that from a previous study of human FL and AB erythroid development, and meta-analysis was performed on the combined dataset. FL erythroid cells showed enhanced proliferation and elevated fetal hemoglobin relative to AB cells. A total of 1,391 fetal up-regulated and 329 adult up-regulated genes were identified from microarray data generated in this study. Five hundred ninety-nine fetal up-regulated and 284 adult up-regulated genes with reproducible patterns between this and a previous study were identified by meta-analysis of the combined dataset, which constitute a core set of genes differentially expressed between FL and AB erythroid cells. In addition to these core genes, 826 and 48 novel genes were identified only from data generated in this study to be FL up- and AB up-regulated, respectively. The relevance for some of these novel genes was demonstrated by pathway analysis, which showed novel genes functioning in pathways known to be important in proliferation and erythropoiesis, including the mitogen-activated protein kinase (MAPK) and the phosphatidyl inositol 3 kinase (PI3K)-Akt pathways. The genes with upregulated expression in FL cells, which include many novel genes identified from data generated in this study, suggest that cellular proliferation pathways are more active in the fetal stage. Erythroid progenitor cells may thus undergo a reprogramming during ontogenesis in which proliferation is modulated by changes in expression of key regulators, primarily MYC, and others including insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3), neuropilin and tolloid-like 2 (NETO2), branched chain amino acid transaminase 1 (BCAT1), tenascin XB (TNXB) and proto-oncogene, AP-1 transcription factor subunit (JUND). This reprogramming may thus be necessary for acquisition of the adult identity and switching of hemoglobin expression.